Etching, dielectric and third order nonlinear optical studies on Czochralski grown Bi2ZnB2O7 single crystal. (23rd February 2017) - Sukumar, M.; Ramesh Babu, R.; Ramamurthi, K.
Abstract : Melilite-type crystal Bi2 ZnB2 O7 was grown by the Czochralski technique from stoichiometric composition of melt. The vibrational frequencies of various functional groups of Bi2 ZnB2 O7 crystal have been derived from Fourier transform infrared and laser Raman analyses. Optical homogeneity and conoscopic interferogram of the grown Bi2 ZnB2 O7 crystal are studied by birefringence interferometric technique. Chemical etching studies were made on Bi2 ZnB2 O7 crystal faces in order to understand the growth mechanism. Third-order nonlinear optical properties of Bi2 ZnB2 O7 crystal are studied using Z–scan technique and the obtained results indicate the self-defocusing behaviour of the grown crystal. Further, the dielectric behaviour of Bi2 ZnB2 O7 crystal is studied.